Numerical Investigation of the Influence of Welding Parameters on Quality of Laser Welded 304L Stainless Steel Sheets - Nuepaul D. Kortu; Bruno Roberts; Rehema Ndeda; Abdel‐Monem El‐Batahgy (Engineering Reports)
ABSTRACT 304L Austenitic stainless steel (ASS) is preferred for various industrial applications, including gas, petroleum, petrochemicals, fertilizers, and food processing, due to its inherent corrosion resistance. Traditionally, arc welding processes have been widely used in the manufacturing of 304L austenitic stainless‐steel components and structures. However, these methods are more likely to cause carbide precipitation and distortion due to their higher heat input compared to laser welding. Despite its advantages, laser welding requires precise parameters to achieve a suitable weld. In this study, a finite element (FE) model was developed to investigate the impact of laser power and welding speed on the weld quality of 304L ASS with a thickness of 3 mm. The model was validated through experimental methods by using a CO2 laser beam to create a full penetration butt weld. The results indicated that the welding heat input is the main factor influencing the quality of welded joints. Laser power and welding speed of 4 kW and 3 m/min, respectively, improved penetration depth and reduced weld width. These findings provide valuable insights for optimizing laser welding parameters to achieve the desired penetration depth, ensuring high‐quality welds in industrial applications.